Be Careful of What You Wish For: The Cultural Politics of Capital Punishment - Ewick, Patricia (Social justice, 2017)
The article presents an analysis of the book "Executing Freedom: The Cultural Life of Capital Punishment in the United States" by Daniel LaChance. Topics discussed include fictional and nonfictional accounts of crime and punishment analyzed by LaChance, irony observed by LaChance at the end of his analysis, and prediction made by LaChance on the death penalty.